Bacteriological profile and outcome of Ventilator associated pneumonia in Intensive care unit of a tertiary care centre - Ravi, K; Maithili, TM; Thomas, David Mathew; Pai, Sphoorti P (Asian Journal of Medical Sciences, 2017)
Background: Ventilator associated pneumonia (VAP) complicates the course of 8-28% of patients receiving mechanical ventilation. Appropriate antimicrobial treatment significantly improves the outcome. Hence rapid identification of infected patients and accurate selection of antimicrobials are important clinical goals. Aims and Objectives: The present study was conducted with an aim to know the outcome of VAP and to identify pathogens, compare the bacteriological profile, duration of mechanical ventilation and length of hospitalization. Materials and Methods: Sixty patients who developed VAP during our study period of 2 years were included after meeting inclusion and exclusion criteria. Study was conducted in Victoria hospital and Bowring & Lady Curzon hospitals attached to Bangalore Medical College and Research institute. Results: Majority of patients were in the age group of 21-40 years. The occurrence of late VAP was 70 %. Klebsiella was the most common organism isolated in our study. Mortality was 13.3%. Average duration of intubation was 13.1±6.6days. Duration of hospital stay was 16.2±7.1 days. Conclusion: Our study concluded that occurrence of late VAP was more common than early VAP. Targeted strategies aimed at preventing VAP should be implemented to improve patient outcome and length of hospitalisation. Above all utmost importance must be given to prevent VAP. Asian Journal of Medical Sciences Vol.8(5) 2017 75-79